Healthy Eating for Elders: Fluids - Linda B. Bobroff; Luisa Oliver-Cordero; Emily Minton (EDIS)
Revised! FCS8569, a 2-page fact sheet by Linda B. Bobroff, Luisa Oliver-Cordero, and Emily Minton, answers several questions about water, fluid intake, and dehydration for elders. Published by the UF Department of Family Youth and Community Sciences, November 2009.